ILO’s Effort against Maritime Labor Crimes: Case of Sexual Harassment on Filipino Women Seafarers - Yordan Gunawan; Ahmad Fahmi Ilham Mulloh (Universitas Muhammadiyah Purwokerto, 2023)
The professions of seafarer and mariner are stereotypically associated with men and have a good employee culture. Traditionally, young people have been allowed on a ship so that they may be directed and socialized to live at sea, yet women and minority groups are particularly vulnerable to sexual harassment in the aforementioned work environment. At the level of policy, both of which compel employers to detect and avoid hazards to occupational safety and health in the workplace. Unfortunately, there has been no separate discussion from the general discussion about sexual harassment on the ship. Secondly, law enforcement and policy in this regard are weak, given the different laws that can be proposed in social aspects. Accordingly, the nature of the research led to the application of the normative method. The result of the research is the International Labor Organization’s (ILO) efforts to combat sexual harassment in the work environment and the importance of adopting and ratifying Recommendation No. 206 and Convention No. 190 to provide a clear framework for action and opportunities to build a dignified work environment and free from sexual harassment.Keywords: Sexual Harassment, Filipino Women Seafarers, ILO, 190 Convention